Community-Based Interventions to Reduce Stigma Toward Families of People with Schizophrenia - Anipah; Asmeriyani (PT FORMOSA CENDEKIA GLOBAL, 2026)
Social stigma toward families of people with mental disorders (ODGJ), particularly schizophrenia, remains a significant issue in communities and negatively affects social support and family well-being. This community service activity aimed to improve public understanding and reduce stigma toward families of people with schizophrenia through community-based interventions. The implementation methods included mental health education, counseling about schizophrenia, and community discussions involving residents in the Jambi City area. The activity was conducted over one month through preparation, implementation, and evaluation stages using a simple questionnaire. The results indicated increased community knowledge and more positive attitudes toward families of people with mental disorders. Community-based interventions demonstrate potential to strengthen social support and enhance community acceptance of families of people with schizophrenia.